Comprehensive technical and economic evaluations of using second-life batteries as energy storage in off-grid applications: A customized cost analysis - Turan, Feyza; Boynuegri, Ali Rifat; Durmaz, Tunc (ELSEVIER, 2025)
The widespread use of lithium-ion batteries has raised significant waste management challenges, exacerbated by limited integration into recycling systems. When functional batteries are discarded rather than repurposed, valuable resources are lost. The emerging second-life battery (SLB) market presents a promising solution. However, uncertainties in SLB pricing significantly impact their economic viability and feasibility. Accurate pricing of SLB can mitigate substantial losses faced by electric vehicle (EV) users during battery replacements, addressing a major barrier to wider EV adoption. This study introduces a novel approach by employing a dynamic degradation model to determine the cycle life and optimize the capacity of both new and second-life batteries, while also considering round-trip efficiency. A comprehensive economic evaluation using the Net Present Value (NPV) method incorporates detailed cost factors, including purchase, testing, renovation, transportation, replacement costs (calculated using the Sinking Fund method), recycling revenues, and the often-overlooked opportunity cost. Additionally, government incentives are integrated into the analysis, resulting in a robust mathematical framework for pricing SLB. SLB market price under 0 %, 25 %, and 50 % government incentives are calculated as 88.05 /kWh, 105.5 /kWh, and 131.60 /kWh, respectively, representing 34.1 % to 54.1 % of new battery purchase costs. The OEM ownership model shows that accounting for opportunity costs makes SLB 44.9 % more profitable than new batteries. Additionally, a sensitivity analysis was conducted to examine the impact of testing, renovation, and transportation costs, recycling revenue, new battery purchase cost, and discount rate parameters on the NPV of off-grid SLB applications and SLB market pricing. The analysis reveals that the new battery purchase cost has the greatest influence on SLB pricing, while the impact of other parameters is significantly lower. This study highlights the importance of dynamic modeling and comprehensive economic evaluation, emphasizing the need for tailored analyses for each application. These findings provide valuable insights into realistic SLB pricing, enhancing their market potential and supporting broader EV adoption.
Keywords: Second-life batteries; Reuse; Battery degradation; Energy storage system; Economic analysis; VEHICLE-BATTERIES; LIFE; SYSTEM; Energy & Fuels